Role of occupational health in managing non-communicable diseases in Brunei Darussalam - Pg Khalifah Pg Ismail; David Koh (Taylor & Francis Group, 2014)
Like most ASEAN countries, Brunei faces an epidemic of non-communicable diseases. To deal with the complexity of NCDs prevention, all perspectives - be it social, familial or occupational - need to be considered. In Brunei Darussalam, occupational health services (OHS) offered by its Ministry of Health, among others, provide screening and management of NCDs at various points of service. The OHS does not only issue fitness to work certificates, but is a significant partner in co-managing patients' health conditions, with the advantage of further management at the workplace. Holistic approach of NCD management in the occupational setting is strengthened with both employer and employee education and participation, targeting several approaches including risk management and advocating healthy lifestyles as part of a healthy workplace programme.